1999
DOI: 10.1130/0091-7613(1999)027<0319:lbohtt>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Link between oceanic heat transport, thermohaline circulation, and the Intertropical Convergence Zone in the early Pliocene Atlantic

Abstract: Planktonic foraminiferal oxygen isotope records from the western and eastern tropical Pacific and Atlantic Oceans suggest a southward shift in the Intertropical Convergence Zone toward its modern location between 4.4 and 4.3 Ma. A concomitant shift in the carbon isotope compositions of Atlantic benthic foraminifera provides strong evidence for an increased thermohaline overturn at this time. We suggest that the southward shift of the Intertropical Convergence Zone and associated change in trade-wind circulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 21 publications
5
53
1
1
Order By: Relevance
“…Atlantic Deep Water (NADW) production during the late Miocene (Blanc et al, 1980;366 Delaney, 1990;Keller and Barron, 1983;Miller and Fairbanks, 1985;Woodruff and Savin, 367 1989;Wright et al, 1992) whilst others indicate a significant increase in the early Pliocene 368 implying weaker production during the Miocene (Billups et al, 1999;Haug and Tiedemann, 369 1998;Tiedemann and Franz, 1997), consequently we are unable to discount either model 370 result. Modelling studies have also demonstrated a significant impact of vegetation on 371 overturning circulation through changes in the hydrological cycle (Ganopolski et al, 1998;372 Zhou et al, 2012).…”
Section: But Did Not Separate Out the Effects Of Vegetation 57mentioning
confidence: 52%
“…Atlantic Deep Water (NADW) production during the late Miocene (Blanc et al, 1980;366 Delaney, 1990;Keller and Barron, 1983;Miller and Fairbanks, 1985;Woodruff and Savin, 367 1989;Wright et al, 1992) whilst others indicate a significant increase in the early Pliocene 368 implying weaker production during the Miocene (Billups et al, 1999;Haug and Tiedemann, 369 1998;Tiedemann and Franz, 1997), consequently we are unable to discount either model 370 result. Modelling studies have also demonstrated a significant impact of vegetation on 371 overturning circulation through changes in the hydrological cycle (Ganopolski et al, 1998;372 Zhou et al, 2012).…”
Section: But Did Not Separate Out the Effects Of Vegetation 57mentioning
confidence: 52%
“…Moreover, support for an early Pliocene southward shift of the ITCZ comes from studies that investigated Atlantic and Pacific changes in tropical wind field and surface hydrography (Hovan, 1995;Farrell et al, 1995;Cannariato and Ravelo, 1997;Chaisson and Ravelo, 1997;Norris, 1998;Billups et al, 1998Billups et al, , 1999. Similar to the modern seasonal cycle, a shift to a more southern position of the ITCZ in the TEP would have weakened the southeast trades and thus significantly reduced the strength of the NECC and the SEC.…”
Section: S Steph Et Al Tropical East Pacific Upper Ocean Stratificamentioning
confidence: 99%
“…In addition, progressive shoaling of the CAS was suggested to trigger changes in atmospheric circulation, such as a strengthening of Walker Circulation over the Pacific and changes in the trade wind strength that might have influenced Pacific surface current systems and the structure of the upper water column, as suggested by Hovan (1995), Cannariato and Ravelo (1997), Billups et al (1999), and Chaisson and Ravelo (2000). Closure-induced warming of the Caribbean basins after 4.6-4.4 Ma (Steph et al, in press) may have caused development of a pressure contrast between the western tropical Atlantic and the eastern tropical Pacific (Chaisson and Ravelo, 2000).…”
Section: S Steph Et Al Tropical East Pacific Upper Ocean Stratificamentioning
confidence: 99%
“…It is unlikely that wind patterns were markedly different at the time of deposition of all the localities because (1) the ITCZ (whose seasonal movement drives the formation of wind-jets) reached it's modern position around 4.4 Ma (Billups et al, 1999), and (2) the obliquity of the earth away from the sun, although less in the Pliocene than it is today (Naish et al, 2009), would have been enough to ensure that the ITCZ passed seasonally over the Burica region. We also reject that mountains were high enough to have blocked wind-jet formation because Cocos Ridge subduction (Corrigan et al, 1990) did not begin until the Pleistocene (Collins et al, 1995;Leon-Rodriguez, 2007).…”
Section: Paleogeographic Implicationsmentioning
confidence: 99%